1998
DOI: 10.1063/1.367288
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and microwave dielectric properties of epitaxial SrTiO3 films on LaAlO3 substrates

Abstract: Sr-deficient and stoichiometric epitaxial (001) SrTiO3 films, deposited on (110)rhombohedral LaAlO3 substrates by rf magnetron sputtering, have been characterized using high-resolution transmission electron microscopy. A subsequent heat treatment in oxygen had a positive influence on the dielectric properties. Sr-deficiency had a large negative impact on the microwave dielectric constant of the films. These changes were correlated to changes in lattice parameters. In all samples, at the film/substrate interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The dielectric susceptibility of the ST films also has a tendency toward an increase with decreasing temper ature, but the curve of the temperature dependence of the dielectric susceptibility demonstrates saturation at temperatures below 100 K [39][40][41]; consequently, the frequency of the polar soft mode does not reach such a low value as in the crystal and ceases to change at 62 cm -1 [42][43][44]. In this respect, several possible fac tors responsible for this behavior of the dielectric sus ceptibility of the ST films have been discussed in the literature: (a) the influence of an intermediate layer (dead layer) between the film and the electrode [39,40,45,46]; (b) mechanical stresses generated by the substrate [46]; and (c) disturbance of the stoichiome try, the porosity, and the presence of grain boundaries in polycrystalline films [45][46][47]. Investigations of the Raman scattering and IR reflection spectra of several polycrystalline ST films have revealed that the pres ence of polar boundaries in polycrystalline ST films leads to a significant increase in the frequency of the soft mode, and it is this shift of the soft mode which represents a fundamental mechanism responsible for the significant decrease in the dielectric susceptibility of the films [48].…”
Section: Raman Irmentioning
confidence: 99%
“…The dielectric susceptibility of the ST films also has a tendency toward an increase with decreasing temper ature, but the curve of the temperature dependence of the dielectric susceptibility demonstrates saturation at temperatures below 100 K [39][40][41]; consequently, the frequency of the polar soft mode does not reach such a low value as in the crystal and ceases to change at 62 cm -1 [42][43][44]. In this respect, several possible fac tors responsible for this behavior of the dielectric sus ceptibility of the ST films have been discussed in the literature: (a) the influence of an intermediate layer (dead layer) between the film and the electrode [39,40,45,46]; (b) mechanical stresses generated by the substrate [46]; and (c) disturbance of the stoichiome try, the porosity, and the presence of grain boundaries in polycrystalline films [45][46][47]. Investigations of the Raman scattering and IR reflection spectra of several polycrystalline ST films have revealed that the pres ence of polar boundaries in polycrystalline ST films leads to a significant increase in the frequency of the soft mode, and it is this shift of the soft mode which represents a fundamental mechanism responsible for the significant decrease in the dielectric susceptibility of the films [48].…”
Section: Raman Irmentioning
confidence: 99%
“…The dielectric constant was calculated as 75 with negligible leakage current <10 À8 A at 5 V bias voltage, which is comparable to other sputter deposited STO thin films. [38][39][40][41][42] Figure 1(c) demonstrated the AFM image of NiFe (1.2 nm)/STO (50 nm) heterostructure with 3 nm Cu cap layer, showing a smooth surface with a low surface roughness of 0.88 nm. Figure 2(a) shows the schematic of FMR measurements of a NiFe (1.2 nm)/STO (50 nm) multiferroic heterostructure by applying voltage from À5 V to 5 V in an X-band (9.55 GHz) ESR system.…”
mentioning
confidence: 96%
“…The STO films were grown on (111)Pt/ (100)Si substrates by RF magnetron sputtering at 400 C and then annealed at 600 C for 2 h at low pressure of 10 À7 Torr. [38][39][40][41][42] The NiFe films of a 400 lm-diameter were sputtered onto the STO films at room temperature. 3 nm Cu was deposited on each NiFe layer as the capping layer.…”
mentioning
confidence: 99%
“…1͒ and a residual interfacial compressive in-plane strain of 0.2%-0.4%. 13 The subgrain boundaries were found to coincide with misfit dislocations at the film/substrate interface, which indicated a correlation between strain and columnar structure. Further, 15%-20% of Sr-deficiency resulted in an enlarged out-of-plane ͑001͒ lattice parameter and deteriorated dielectric properties, where the dielectric constant was lowered from 800 to 500 ͑at 1 MHz, 77 K͒.…”
Section: Introductionmentioning
confidence: 90%
“…The film was fabricated from a nonstoichiometric STO target, with the composition Sr 1.1 Ti 0.9 O 3 , which had earlier been shown to result in stoichiometric films. 12,13 The STO and YBCO film thicknesses were 150 and 75 nm, respectively. However, the STO and YBCO targets were placed on either side of the substrate, which gave a variation of the layer thicknesses across the substrate, with a variation of about Ϯ5%.…”
Section: Methodsmentioning
confidence: 99%